2020
DOI: 10.1186/s12909-020-02319-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported confidence and perceived training needs of surgical interns at a regional hospital in Ghana: a questionnaire survey

Abstract: Background Due to disparities in their regional distribution of the surgical specialists, those who have finished “housemanship,” which is the equivalent of an internship, are serving as main surgical care providers in rural areas in Ghana. However, the quantitative volume of postgraduate surgical training experience and the level of self-reported confidence after formal training have not been investigated in detail in sub-Saharan Africa. Methods The quality-assessment data of the Department of surgery at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Fonseca AL, et al reported that lack of confidence of graduating general surgery residents in performing open vascular maneuvers varied regionally and was associated with both demographic and program-specific factors [ 8 ]. Kang MJ, et al described that because there are the disparities in their regional distribution of the surgical specialists in Ghana, the current state of training at teaching hospitals should be investigated to decide where and how long the surgical rotation should take place [ 9 ]. A nationwide questionnaire survey on acquisition of Board-Certified Surgeon status in the Japan Surgical Society showed that surgeons in regional areas tend to have less experience with surgical operations and fewer opportunities to undergo regular off-the-job training outside the operating room than those in urban areas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca AL, et al reported that lack of confidence of graduating general surgery residents in performing open vascular maneuvers varied regionally and was associated with both demographic and program-specific factors [ 8 ]. Kang MJ, et al described that because there are the disparities in their regional distribution of the surgical specialists in Ghana, the current state of training at teaching hospitals should be investigated to decide where and how long the surgical rotation should take place [ 9 ]. A nationwide questionnaire survey on acquisition of Board-Certified Surgeon status in the Japan Surgical Society showed that surgeons in regional areas tend to have less experience with surgical operations and fewer opportunities to undergo regular off-the-job training outside the operating room than those in urban areas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,24,25 Admittedly the present study bears the limitation of evaluating the self-perceived confidence of the students. Although it is considered that there is a positive correlation between reported confidence and clinical experience, 26 self-assessment of surgical skills may be inaccurate, 27 particularly in those who perform poorly. 28 Moreover, overconfident graduates can put their patients at risk when carrying out surgical procedures without actual competency.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation adopts evolutionary algorithm, fuzzy comprehensive evaluation, multivariate statistical analysis method, etc., to obtain effective weights, and the data items are summed according to the weights to obtain the quantitative score evaluation value [ 16 ]. Kang et al selected some data from a large-scale data set, used these data to construct an adjacency matrix, and obtained eigenvectors by eigendecomposition of the adjacency matrix, and finally used Nyström to approximate the eigensolution of the original matrix [ 17 ]. Aiming at the main methods of DM, Hou et al studied the ideas and applications of related algorithms, analyzed the advantages and disadvantages of existing methods and compared them.…”
Section: Related Workmentioning
confidence: 99%